The Effect of Aerobic Exercise on Collagen Type I and IV Gene Expression and Collagen Type I Protein Changes in the Sciatic Nerve of Diabetic Rats - Jalilian Hamed, Nahid; Gharakhanlou, Reza; Peeri, Maghsoud (Novelty in Biomedicine, 2020)
Background: Neuropathy is one of the complications of diabetes, probably due to the destruction of the extracellular matrix and the thickening of the peripheral nerve basement membrane. However, its mechanisms and the impact of exercise on these disorders has not fully understood. The purpose of the present study was to investigate the effect of aerobic exercise on collagen levels of type I and IV and collagen type I protein changes in the sciatic nerve of diabetic rats. Materials and Methods: Eighteen 10-week-old Wistar male rats weighing 250 ± 20 g were randomly divided into three groups of healthy control (n=6), diabetic (n=6) and diabetic + aerobic exercise (n=6). For this purpose, after introduction and adaptation of rats to new environment, diabetes was induced by single dose injection of dissolved streptozotocin in sodium citrate buffer at pH=4.5 at 45 mg/kg intraperitoneal. After confirming neuropathic conditions (with behavioral tests), diabetic+exercise rats underwent moderate-intensity aerobic exercise on the treadmill for 8 week. At the beginning and at the end of the period, blood glucose of all rats was measured by glucometer and the mean of each group was measured separately. Changes in collagen type I and IV gene expression, and collagen type I protein levels in sciatic nerve of rats were evaluated by real-time PCR technique and immunohistochemistry, respectively. Results: Diabetes increased collagen type I and IV gene expression and collagen type I protein levels in the sciatic nerve samples of rats. However, exercise reduced blood sugar levels and expression of collagen type I and IV genes (p=0.05) and collagen type I protein significantly reduced in sciatic nerve (p=0.001). Conclusion: The results of the present study showed that aerobic exercise as a non-pharmacological strategy by negative regulating type I and IV collagen factors at the gene and protein level, was able to control and inhibit the effects of diabetes on extracellular matrix components in the sciatic nerve.